Command and Control of Discrete-Event Systems: Towards Online Hierarchical Control Based on Feasible System Decomposition - Ngo, Quang Ha (2016)
A new operational design for hierarchical control of discrete-event systems is proposed. The design brings the structure of command and control from concept to realization for online control operation. For a command reference input, a new concept for output control feasibility of a discrete-event system modeled by a Moore automaton is characterized; and a system decomposition of a suitably structured Moore automaton into a controllable subsystem and an uncontrollable subsystem is formulated. Based on these results, the new command and control design for controller operation is realized, examined, and discussed.